Glue Sniffing Among the Street Children Residing at Pokhara Metropolitan, Nepal: A Descriptive Cross-sectional Study - Acharya, Anil; Shrestha, Naveen; Paudel, Shishir (Journal of Nepal Paediatric Society, 2022)
Introduction: Glue sniffing usually refers to volatile substance abuse (VSA) for psychoactive effects. Street children are the children who live, work, and earn their livelihood through the streets of urban settlements. Street children are mostly attracted to substance abuse and more particularly towards volatile substances as they are cheap, easy to access and have psychoactive effects as alcohol intoxication. This study aimed to assess the general characteristics of street children of Pokhara Metropolitan, Nepal who are addicted to glue sniffing. Methods: A cross-sectional study was conducted among street children who were addicted to glue sniffing through the snowball sampling method in Pokhara Metropolitan, Nepal. Results: All 88 children who were addicted to glue sniffing were males. Of the total children, 59 (67%) children started glue-sniffing at the age of five to ten years of age while nine (10.2%) children started sniffing even before they were five years old. Addiction to glue (n = 33, 37.5%), pleasure (n = 18, 20.5%)), coping with hunger (n = 14, 15.9%), and being a part of street children group (n = 13, 14.8%) were the major reasons to sniff glue for these children. Conclusions: It has been observed that the majority of street children are at increased risk of getting involved in glue sniffing. It has resulted in different ill outcomes such as self-destruction and problematic behavior, fights and police arrest. There is a need to focus on the issue of glue sniffing among the street children to save and ensure the quality of life of these vulnerable children.